2014
DOI: 10.3171/2014.8.jns13515
|View full text |Cite
|
Sign up to set email alerts
|

Presence of matrix metalloproteinase–2 and tissue inhibitor matrix metalloproteinase–2 gene polymorphisms and immunohistochemical expressions in intracranial meningiomas

Abstract: ObjectMeningiomas are benign extraaxial tumors with a slow progression. Some of them, in spite of being benign in nature, may show an aggressive progression pattern. To investigate the behavioral characteristics of meningiomas, researchers have studied matrix metalloproteinases (MMPs), their tissue inhibitors (TIMPs), interstitial collagens, proteins, vascular endothelial growth factors (VEGF), and tumor necrosis factors.MethodsIn this study, the authors investigatedMMP2andTIMP2gene polymorphisms in formalin-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…In the last few years, the role played by MMP‐2 and MMP‐9 in neoplastic progression of meningioma in humans has been considered marginal to basic, and there is more support for the ratio of metalloproteinases to their inhibitors to be more specifically involved in extracellular matrix enzymatic degradation. Most recently, a marked imbalance between MMP‐2 and TIMP‐2 has been more closely associated with meningioma progression . In our study, descriptive statistics did not show significant differences of MMP‐2/TIMP‐2 ratio associated with the morphologic progression of tumors, perhaps suggesting alternative molecular pathways involved in MMP‐2 expression or biologic variation between meningiomas in dogs and humans.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…In the last few years, the role played by MMP‐2 and MMP‐9 in neoplastic progression of meningioma in humans has been considered marginal to basic, and there is more support for the ratio of metalloproteinases to their inhibitors to be more specifically involved in extracellular matrix enzymatic degradation. Most recently, a marked imbalance between MMP‐2 and TIMP‐2 has been more closely associated with meningioma progression . In our study, descriptive statistics did not show significant differences of MMP‐2/TIMP‐2 ratio associated with the morphologic progression of tumors, perhaps suggesting alternative molecular pathways involved in MMP‐2 expression or biologic variation between meningiomas in dogs and humans.…”
Section: Discussioncontrasting
confidence: 51%
“…To date, in meningiomas of dogs, MMPs have been investigated with phenotyping studies (e.g., immunohistochemistry) instead of genotyping studies, and specific investigations of MMP/TIMP ratios have not been reported. The MMP‐2/TIMP‐2 expression ratio has been considered a critical factor in the invasion and metastasis of mouse renal cell carcinoma, and MMP‐2 and TIMP‐2 polymorphisms have been considered genetic mechanisms of meningioma pathogenesis in humans …”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that MMP2 and TIMP2 are involved in the migration and invasion processes of H8 cells. The ratio of secreted MMP2/TIMP2 serves as a better indicator of invasiveness than measurements of each index alone (Coven et al, ). Treatment with edaravone alone resulted in a higher MMP2/TIMP2 ratio, indicating a stimulatory effect on H8 invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…TIMP‐2, the main endogenous inhibitor of MMP‐2, is responsible for regulating the functions of MMPs . The MMP‐2/TIMP‐2 expression ratio is an important factor in certain nervous and vascular disorders . In our study, the TIMP‐2 (rs2277698) gene polymorphism was shown to be weakly associated with DAVF patients subgrouped by CVR grading ( P = 0.026; OR 3.0 [95% CI 1.1–8.2]).…”
Section: Discussionmentioning
confidence: 53%